THE INFLUENCE OF TECHNOLOGY ACCEPTANCE AND MOTIVATION ON THE INTENTION TO BECOME A TIKTOK AFFILIATOR - Mookda, Rarina; Chotchoung, Sirikanya; Wongtep, Amaravedee (Journal of MCU Nakhondhat, 2026)
This research aims to 1) Study the level of intention to become a sales agent through the TikTok application and 2) Study the factors of technology acceptance and motivation that influence the intention to become a sales agent through the TikTok platform. A quantitative research method was used, with the study population being TikTok users in Thailand. The sample size was determined using the G*Power program for multiple regression analysis, with 7 independent variables. The calculation indicated that a minimum of 153 people should be included to increase the reliability and sufficiency of the statistical analysis. The researcher collected 200 data sets using an online questionnaire as the data collection tool. Reliability testing was performed using Cronbach’s Alpha analysis. Data analysis used frequency distribution, percentages, descriptive statistics including the arithmetic mean and standard deviation, as well as stepwise multiple regression analysis. The research results showed that technology acceptance factors, in terms of perceived benefits, and motivation factors, including passion, job security, and compensation, had a statistically significant positive influence on the intention to become a sales agent through TikTok. All variables combined can predict 70.3% of the variance in this intention (R² = .703), reflecting that these factors can explain a high degree of variance in the intention to become an online broker. This can be used as a guideline for entrepreneurs, digital platforms, and relevant agencies in developing strategies to promote online brokerage and support the creation of income opportunities in Thailand’s digital economy.